The HIV/AIDS pandemic in South Africa: sectoral impacts and unemployment - Arndt, Channing; Lewis, Jeffrey D. (Wiley, 2001)
South Africa is currently confronting an HIV/AIDS crisis. HIV prevalence in the population is currently estimated at about 13 per cent with that number projected to increase over the next five years or so. Given the massive scale of the problem and the concentration of effects on adults of prime working age, the pandemic is expected to sharply influence a host of economic and non‐economic variables. While the pandemic will certainly influence the rate of economic growth, structural changes are also likely to be one of the primary economic hallmarks of the AIDS pandemic.This paper builds on the work of Arndt and Lewis (2000) who estimated the aggregate macroeconomic impacts of the HIV/AIDS pandemic in South Africa using a computable general equilibrium (CGE) approach. They found that, despite dramatically lower rates of growth of the unskilled labor pool relative to the ‘no AIDS’ trend, estimated unemployment rates for unskilled labor in their base ‘AIDS’ scenario increased absolutely over most of the upcoming decade and are essentially the same (slightly higher in fact) as the rates estimated for a fictional ‘no AIDS’ scenario. In this paper, we seek to further investigate the interactions between unemployment and AIDS using the basic modeling approach set forth in Arndt and Lewis.Before projecting the impacts of the pandemic on unemployment, recently compiled historical data on employment, unemployment, and remuneration are presented. The unemployment problem is, rather, an employment problem; and it is concentrated primarily in the unskilled and semi‐skilled labour category. Job creation performance over the past three decades in this category has been dismal with total employment (formal sector and informal sector) of unskilled and semi‐skilled labourers in 1999 at only 92 per cent of the level present in 1970.In a country with an extraordinarily complex historical legacy such as South Africa, it is impossible to attribute this disastrous job creation performance to any single factor. Nevertheless, large differences in remuneration trends across labor classes and standard economic theory point to these trends as major contributing factors. By 1999, real remuneration per unskilled and semi‐skilled worker had grown to 250 per cent of the 1970 level while remuneration for other categories had remained essentially flat. Based on these data, the neoclassical conclusion that unskilled and semi‐skilled labor has been systematically pricing itself out of the market seems practically unavoidable. Employment growth has, given slow economic growth rates, gone hand in hand with wage moderation as in the highly skilled and skilled segments. In contrast, employment compression has been associated with substantial real remuneration growth as in the unskilled and semi‐skilled segment.With this historical background in mind, we turn to examining the interactions between the AIDS pandemic and unemployment using a CGE approach. In the model, the unskilled and semi‐skilled wage is fixed relative to the producer price index. As a result, employment levels by activity are the equilibrating variables. We find that, even though the pandemic is projected to drive growth rates in the supply of unskilled and semi‐skilled labour to around zero, our analysis indicates that the pandemic will also depress labour demand leaving the unemployment rate, in our base ‘AIDS’ scenario, essentially unchanged compared with a fictional ‘no AIDS’ scenario. The pandemic depresses labour demand through three effects. Declines in the rate of overall economic growth. Pronounced declines in sectors that supply investment commodities, particularly the Construction and Equipment sectors. These two sectors happen to use unskilled and semi‐skilled labour intensively and together account for a significant share (16.3 per cent) of total payments to this category of labour. Beyond this investment demand effect (brought on by reduced savings), AIDS induced morbidity effects on unskilled and semi‐skilled workers tend to depress output relatively more in sectors that use unskilled and semi‐skilled labour intensively with further negative implications for employment.Declines in the rate of overall economic growth.Pronounced declines in sectors that supply investment commodities, particularly the Construction and Equipment sectors. These two sectors happen to use unskilled and semi‐skilled labour intensively and together account for a significant share (16.3 per cent) of total payments to this category of labour.Beyond this investment demand effect (brought on by reduced savings), AIDS induced morbidity effects on unskilled and semi‐skilled workers tend to depress output relatively more in sectors that use unskilled and semi‐skilled labour intensively with further negative implications for employment.Countering these three effects will be key to palliating the negative economic consequences of the pandemic and reducing unemployment rates. To reduce the unemployment problem, South Africa must have rapid overall economic growth ideally with sectors that use unskilled and semi‐skilled labour intensively leading the way. Results indicate that a policy of real wage moderation (or even modest decline) presents a straightforward option for bolstering overall economic growth. A wage moderation policy also provides a particularly large stimulus for sectors that use unskilled and semi‐skilled labour intensively with further positive implications for employment. Copyright © 2001 John Wiley & Sons, Ltd.